Changing Trends In Emergency Peripartum Hysterectomy (Journal of Fatima Jinnah Medical University, 2018)
Introduction: EMERGENCY PERIPARTUM HYSTERECTOMY is a life saving procedure performed after spontaneous vaginal delivery or caesarean section, or in the immediate post partum period. Although rare in modern obstetrics, it still remains a life saving procedure in cases of intractable hemorrhage where conservative measures fail, although it itself is still associated with significant maternal mortality and morbidity even in developed countries. Aims and Objectives: The aim of the present study was to determine the indications and complications associated with this procedure. Study Design: This is a descriptive, observational and cross sectional study. Settings: GYNAE UNIT 3, SIR GANGA RAM HOSPITAL.LAHORE Population: All patients who underwent emergency peripartum hysterectomy after Caesarean or spontaneous vaginal delivery in Gynae unit 3 of Sir Ganga ram hospital during the study period from October 2010-October 2014 were included in the study. Methodology: This was a prospective study and main outcome measures were frequency of emergency peripartum hysterctomy, age of the patient, gravidity, parity, and indications. Risk factors associated with emergency peripartum hysterctomy were observed and recorded. The intra and postoperative complications were also recorded. Results: The frequency of EMERGENCY PERIPARTUM HYSTERCTOMY in our study was 0.1974%.The mean age and parity of patients was 29.836% and 4.55% respectively. The mean gestational age at the time of delivery was 30.08 weeks.33 (70%) patients had previous history of caesarean delivery. The main indications of EMERGENCY PERIPARTUM HYSTERCTOMY were abnormally adherent placenta in 23 (60%) cases. Uterine atony in 13(26%) of the cases. Placental bed bleeding in 11(22%) cases and uterine rupture in 5(10%) of the cases. 48(96%) EMERGENCY PERIPARTUM HYSTERCTOMY were total and 2(4%) were subtotal. 44(88%) were carried out after Caeserean section and 6(12%) after SVD. 8(16%) patients had urinary bladder injury and 4(8%) had broad ligament haematoma. All patients required blood transfusions. 44(88%) had haemoglobin less than 11gm/dl after 48 hours of EMERGANCY PERIPARTUM HYSTERCTOMY.7(14%)had ICU admission. 1(2%) had pulmonary oedema and 5(10%) had wound disruption. No maternal mortality was observed in our study. Conclusions: The frequency of emergency peripartum hysterctomy was lower in our setup. The most common indication of emergency peripartum hysterctomy in our study was morbidly adherent placenta. All cases of Morbidly Adherent Placenta were associated with Placenta Previa and history of caesarean sections. There was no maternal mortality in our study. This could be explained by the fact that all emergancy peripartum hysterctomies were carried out by senior obstetricians. So the recommendations are that better antenatal care, presence of experienced staff in emergency, early recognition and management of complications for example placenta previa and uterine atony and avoidance of unnecessary caesarean sections can decrease the incidence of abnormal placentation and placenta previa.
Keywords: Emergency Peripartum Hysterectomy, Abnormal Placentation. Placenta Previa, Maternal morbidity, caesarean section